Analisis Ikon, Indeks, dan Simbol Semiotika Karakter Juki dalam Naskah Sumur Tanpa Dasar Karya Arifin C. Noer - Hanifah, Nida; Saputri, Syaharani; Nugroho, Rudi Adi (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2025)
The theory of semiotics was first coined by two experts, namely Ferdinand de Saussure and Charles Sanders Peirce. In this research, the author uses descriptive qualitative method with Peirce's semiotic approach. The object of this research is the play Sumur Tanpa Dasar by Arifin C. Noer. Sumur Tanpa Dasar is a play that was first performed in 1964 in Yogyakarta. The results show that Juki's character depicts deep symbols about the absurdity of life, time travel, complicated relationships, and thirst for freedom. Of the three forms of signs, icons are found the most. This research makes a new contribution by examining Sumur Tanpa Dasar from the point of view of Peirce's semiotics, which was previously analyzed more with structural approaches and literary psychology. This research is relevant for the development of literature, philosophy, and art studies, as well as a reference for similar research in the future.